Determination of pesticide toxicity parameters using probit-analysis - O. Shevchuk; O. Vlasova; I. Shevchuk; Yu. Stefkivska (Карантин і захист рослин)
Goal of the research is to consider the main concepts used in the probit-analysis method, the features of its application to determine the toxicity of pesticides, in particular insecticides, acaricides and fungicides.